2021
DOI: 10.1021/acs.jmedchem.1c00948
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel, Orally Bioavailable Pyrimidine Ether-Based Inhibitors of ELOVL1

Abstract: In our efforts to identify novel small molecule inhibitors for the treatment of adrenoleukodystrophy (ALD), we conducted a high-throughput radiometric screen for inhibitors of elongation of very long chain fatty acid 1 (ELOVL1) enzyme. We developed a series of highly potent, central nervous system (CNS)-penetrant pyrimidine ether-based compounds with favorable pharmacokinetics culminating in compound 22. Compound 22 is a selective inhibitor of ELOVL1, reducing C26:0 VLCFA synthesis in ALD patient fibroblasts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Age-related hypermethylation and ELOVL2 could act as links between early developmental phases and aging. This involvement of ELOVL2 could be further investigated in future clinical and forensic research. , A particular form of ELOVL3 is related to the skin. Studies in mice lacking ELOVL3 demonstrated that ELOVL3 is necessary for the production of neutral lipids in the skin, wherein these mice had significant water-repelling abnormalities, increased trans-epidermal thin-hair coats, water loss, and hyperplastic pilosebaceous systems.…”
Section: Elovl: Additional Family Membersmentioning
confidence: 99%
See 2 more Smart Citations
“…Age-related hypermethylation and ELOVL2 could act as links between early developmental phases and aging. This involvement of ELOVL2 could be further investigated in future clinical and forensic research. , A particular form of ELOVL3 is related to the skin. Studies in mice lacking ELOVL3 demonstrated that ELOVL3 is necessary for the production of neutral lipids in the skin, wherein these mice had significant water-repelling abnormalities, increased trans-epidermal thin-hair coats, water loss, and hyperplastic pilosebaceous systems.…”
Section: Elovl: Additional Family Membersmentioning
confidence: 99%
“…It decreases C26:0 VLCFA production in fibroblasts and lymphocytes from ALD patients. The compound’s biochemical and cellular activity was found to be further elevated when the pyridine core was switched with a pyrimidine ring using HEK293, an immortalized human embryonic kidney cell line …”
Section: Elovl1 As a Potent Pharmacological Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…Until present, over 2,700 types of mutations have been identified (2). ABCD1 codes the protein of adenosine 5 -triphosphate (ATP) binding cassette subfamily D member 1, which is located in the peroxisomal membrane to transport the very-long-chain fatty acids (VLCFAs) into peroxisomes for β-oxidation (3). The dysfunctional ABCD1 causes the failure of VLCFA degradation (4,5), leading to the accumulation of VLCFA, especially C:26 and C:24 in tissues and plasma, and damage to organs, particularly in the cerebral white matter, spinal cord, and adrenal cortex (6,7).…”
Section: Introductionmentioning
confidence: 99%